Disturbi visivi ed autismo: uno sguardo sulla complessità - Pili, Roberto; Farris, Pericle; Zolo, Bachisio; Petretto, Donatella Rita (UNICApress, 2022)
Over the past three decades, there has been a growing interest in the link between severe visual disorders (low vision and blindness) and the presence of autism spectrum disorders. Starting from an approach that focuses on the centrality of the person and adopts a biopsychosocial perspective, the text aims to investigate this comorbidity, proposing research questions, theoretical reflections, and intervention insights. In particular, the text focuses on the following themes: the importance of sensitive and specific diagnostic tools and pathways for the early detection of visual impairment from the earliest stages of development in people with autism spectrum disorders; the importance of specific intervention approaches that take into account the distinctiveness related to this comorbidity and allow supporting and promoting the developmental potential of people with this comorbidity; and the importance of informing and training, through a collaborative and person-centered approach, family members, caregivers, teachers, educators, pedagogues and other professionals in the field of inclusion.